1983
DOI: 10.1093/ije/12.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Drug Use in Schoolchildren: IV--Factors Associated with Changes in Smoking Behaviour

Abstract: Factors associated with changes in the smoking behaviour of approximately 6000 schoolchildren (two cohorts aged between 10 and 12 years in 1979) over 12 months are described. They were measured twice as part of a randomized controlled trial of a smoking prevention programme. Four groups were defined: (a) those who became smokers (adopters); (b) those who remained non-smokers; (c) those who became non-smokers (quitters), and, (d) those who remained smokers. Personal and social variables were ordered using a log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(39 citation statements)
references
References 0 publications
2
35
1
1
Order By: Relevance
“…Second, several variables that have a demonstrated relationship with smoking were not included: specific efficacy (e.g., Baer, Kamarck, Lichtenstein, & Ramson, 1989), degree to which person feels that their behavior controls their health (e.g., Leventhal & Cleary, 1980), reasons for quitting, temptation coping (Shiffman, 1984), parental disapproval (e.g., Ary, Biglan, Nautel, Weissman, & Severson, 1983;Hansen, Graham, Sobel, Shelton, Flay, & Johnson, 1987), beliefs about the connection between smoking and body weight (Meyers, Klesges, Winders, Ward, Peterson, & Eck, 1997), abstinence maintenance social support (e.g., Horwitz et al, 1985), health beliefs about smoking (e.g., Leventhal, Fleming, & Glynn, 1988), and how much money each week to spend (Alexander, Callcott, Dobson, Hardes, Lloyd, & O'Connell, 1983). Any of these variables may be related to smoking frequency or persistence and should be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, several variables that have a demonstrated relationship with smoking were not included: specific efficacy (e.g., Baer, Kamarck, Lichtenstein, & Ramson, 1989), degree to which person feels that their behavior controls their health (e.g., Leventhal & Cleary, 1980), reasons for quitting, temptation coping (Shiffman, 1984), parental disapproval (e.g., Ary, Biglan, Nautel, Weissman, & Severson, 1983;Hansen, Graham, Sobel, Shelton, Flay, & Johnson, 1987), beliefs about the connection between smoking and body weight (Meyers, Klesges, Winders, Ward, Peterson, & Eck, 1997), abstinence maintenance social support (e.g., Horwitz et al, 1985), health beliefs about smoking (e.g., Leventhal, Fleming, & Glynn, 1988), and how much money each week to spend (Alexander, Callcott, Dobson, Hardes, Lloyd, & O'Connell, 1983). Any of these variables may be related to smoking frequency or persistence and should be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that having parents or siblings who smoke or use illegal drugs in the family increases one's risk of regular smoking (Alexender et al, 1983;Brook et al, 2004;Chassin, Clark, Presson, Sherman, & McGrew, 1986;Denton & Kampfe, 1994;Kierker, Avenevoli, Merikangas, Flaherty, & Stolar, 2001;Eckhardt, Woodruff, & Elder, 1994;Fagan, Brook, Rubenstone, & Zhang, 2005;Flay et al, 1994;Jackson & Henriksen, 1997;Nyari, Heredi, & Parker, 2005;Ohannessian et al, 2004). Although modeling is often cited as the reason for the observed link between smoking among family members, genetic effects may also be at play (Boomsma, Koopmans, Van Doornen, & Orlebeke, 1994;Maes et al, 1999).…”
Section: Family Peer and Environmental Domainsmentioning
confidence: 99%
“…Very few longitudinal studies that prospectively link exposure to tobacco advertising to smoking initiation have been done. Two Australian studies reported higher rates of smoking initiation among youth who 1 or 2 years earlier had indicated approval of cigarette advertising 40 or reported that cigarette advertisements made smoking appear attractive to them. 41 A Scottish study found that youths with higher awareness of, and liking for, cigarette advertisements at baseline were more likely to develop positive intentions to smoke after a 1-year follow-up period, but a significant effect on smoking behavior was not observed.…”
mentioning
confidence: 99%